Inflammatory pre-conditioning restricts the seeded induction of α-synuclein pathology in wild type mice. Issue 1 (December 2017) - Koller, Emily; Brooks, Mieu; Golde, Todd; Giasson, Benoit; Chakrabarty, Paramita
Abstract Background Cell-to-cell transmission of α-synuclein (αSyn) is hypothesized to play an important role in disease progression in synucleinopathies. This process involves cellular uptake of extracellular amyloidogenic αSyn seeds followed by seeding of endogenous αSyn. Though it is well known that αSyn is an immunogenic protein that can interact with immune receptors, the role of innate immunity in regulating induction of αSyn pathology in vivo is unknown. Herein, we explored whether altering innate immune activation affects induction of αSyn pathology in wild type mice. Methods We have previously demonstrated that recombinant adeno-associated virus (AAV) mediated expression of the inflammatory cytokine, Interleukin (IL)-6, in neonatal wild type mice brains leads to widespread immune activation in the brain without overt neurodegeneration. To investigate how IL-6 expression affects induction of αSyn pathology, we injected mouse wild type αSyn fibrils in the hippocampus of AAV-IL-6 expressing mice. Control mice received AAV containing an Empty vector (EV) construct. Two separate cohorts of AAV-IL-6 and AAV-EV mice were analyzed in this study: 4 months or 2 months following intrahippocampal αSyn seeding. Results Here, we show that IL-6 expression resulted in widespread gliosis and concurrently reduced αSyn inclusion pathology induced by a single intra-hippocampal injection of exogenous amyloidogenic αSyn. The reduction in αSyn inclusion pathology in IL-6 expressing mice was time-dependent. Suppression of αSyn pathology was accompanied by reductions in both argyrophilic and p62 immunoreactive inclusions. Conclusions Our data supports a beneficial role of inflammatory priming of the CNS in wild type mice challenged with exogenous αSyn. A likely mechanism is efficient astroglial scavenging of exogenous αSyn, at least early in the disease process, and in the absence of human αSyn transgene overexpression. Given evidence that a pro-inflammatory environment may restrict seeding of αSyn pathology, this can be used to design anti-αSyn immunobiotherapies by harnessing innate immune function.